Inverse-designed terahertz modulators based on semiconductor multilayers. (12th July 2021) - Centeno, E; Alvear-Cabezón, E; Smaali, R; Moreau, A; Taliercio, T
Abstract: Using a global optimization algorithm, differential evolution, we show that optically actuated terahertz (THz) modulators can be designed using multilayers of InAs and GaSb semiconductors. The optical pump is actually able to generate photocarriers which diffuse into the structure and drastically modify its response at THz frequencies. A modulation depth between 63% and 85% is reached in the range of 1–3 THz for a low pump irradiance of 10 W cm −2 in the continuous regime, whether the modulators operate at one or up to four arbitrary chosen frequencies.